2022
DOI: 10.1186/s12889-022-13806-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors in explaining women’s anaemia in limited resource areas: evidence from West Bengal of India and Bangladesh

Abstract: Background Anaemia among women is a public health problem with associated adverse outcomes for mother and child. This study investigates the determinants of women’s anaemia in two Bengals; West Bengal (a province of India) and Bangladesh. These two spaces are inhabitated by Bengali speaking population since historic past. The study argues that open defecation, contraceptive method use and food consumption patterns are playing crucial role in explaining anaemia. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
3
8
0
Order By: Relevance
“…This result was consistent with a study undertaken in Nepal (Gautam et al, 2019), India, and Bangladesh (Jana et al, 2022) where women in households using dug wells as sources of drinking water were significantly associated with an increased risk of developing anemia. In the case of Bangladesh, it was partly attributable to fluoride and arsenic in groundwater (Del Bello, 2020; Jana et al, 2022). In some contexts, it may be due to intestinal worm infections (Chelkeba et al, 2022; WHO, 2022) which cause gut blood losses, malabsorption of nutrients, loss of appetite, and anemia due to loss of iron and impaired protein metabolism (Pullan et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result was consistent with a study undertaken in Nepal (Gautam et al, 2019), India, and Bangladesh (Jana et al, 2022) where women in households using dug wells as sources of drinking water were significantly associated with an increased risk of developing anemia. In the case of Bangladesh, it was partly attributable to fluoride and arsenic in groundwater (Del Bello, 2020; Jana et al, 2022). In some contexts, it may be due to intestinal worm infections (Chelkeba et al, 2022; WHO, 2022) which cause gut blood losses, malabsorption of nutrients, loss of appetite, and anemia due to loss of iron and impaired protein metabolism (Pullan et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Results from the current study indicated that unimproved dug wells as a source of drinking water were a positive predictor of anemia in WRA, with those relying on unimproved dug wells being at a greater risk of anemia than those using improved wells. This result was consistent with a study undertaken in Nepal (Gautam et al, 2019), India, and Bangladesh (Jana et al, 2022) where women in households using dug wells as sources of drinking water were significantly associated with an increased risk of developing anemia. In the case of Bangladesh, it was partly attributable to fluoride and arsenic in groundwater (Del Bello, 2020; Jana et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Three main domains of variables (biodemographic and socioeconomic, behavioural and health related variables) were selected for the study, which are described later in this section. The analysis for this study is based on this conceptual framework adapted from the existing literature on anaemia [ 47 – 53 ]. The conceptual framework is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%